Expanding the donor base in higher education : engaging non-traditional donors - Drezner, Noah D. (New York : Routledge, 2013)
"Traditionally, institutions have relied on wealthy White men to reach their fundraising goals. But as state investment in public higher education lessens and institutions look to philanthropy to move from excellence to eminence, advancement officers continually need to engage all populations, including many that have historically been excluded from fundraising strategies. Based on theory, research, and past practice, Expanding the Donor Base in Higher Education explores how colleges and universities can build culturally sensitive fundraising and engagement strategies. This edited book presents emerging research on different communities that have not traditionally been approached for fundraising including Lesbian, Gay, Bisexual, Transgender, and Queer (LGBTQ) alumni, African Americans, Latinos, graduate students, young alumni, women, and faculty donors. Chapters discuss and analyze successful programs and provide practical suggestions and strategies to create and implement fundraising programs that engage these new donor populations. Expanding the Donor Base in Higher Education is an essential resource for any institution looking to expand their pool of donors and cultivate a more philanthropic mindset among alumni and students"--
section 1. Radical minorities -- section 2. Other alumni constituencies -- section 3. On-campus constituencies and future donors.
Includes bibliographical references and index.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Educational fund raising -- United States; College benefactors -- United States; Electronic books